Multisite spectroscopic seismic study of the β Cep star V2052 Ophiuchi: Inhibition of mixing by its magnetic field - Briquet, M. (2012)
We used extensive ground-based multisite and archival spectroscopy to derive observational constraints for a seismic modelling of the magnetic β Cep star V2052 Ophiuchi. The line-profile variability is dominated by a radial mode (f 1 = 7.14846d -1) and by rotational modulation (P rot = 3.638833d). Two non-radial low-amplitude modes (f 2 = 7.75603d -1 and f 3 = 6.82308d -1) are also detected. The four periodicities that we found are the same as the ones discovered from a companion multisite photometric campaign and known in the literature. Using the photometric constraints on the degrees ℓ of the pulsation modes, we show that both f 2 and f 3 are prograde modes with (ℓ, m) = (4, 2) or (4, 3). These results allowed us to deduce ranges for the mass (M ∈ [8.2, 9.6]M ⊙) and central hydrogen abundance (X c ∈ [0.25, 0.32]) of V2052 Oph, to identify the radial orders n 1 = 1, n 2 = -3 and n 3 = -2, and to derive an equatorial rotation velocity v eq ∈ [71, 75]kms -1. The model parameters are in full agreement with the effective temperature and surface gravity deduced from spectroscopy. Only models with no or mild core overshooting (α ov ∈ [0, 0.15] local pressure scale heights) can account for the observed properties. Such a low overshooting is opposite to our previous modelling results for the non-magnetic β Cep star θ Oph having very similar parameters, except for a slower surface rotation rate. We discuss whether this result can be explained by the presence of a magnetic field in V2052 Oph that inhibits mixing in its interior.